Contouring the accessory parotid gland and major parotid glands as a single organ at risk during nasopharyngeal carcinoma radiotherapy - Cai, Xin-Ling; Hu, Jiang; Shi, Jun-Tian; Chen, Jin-Shu; Bai, Shou-Min; Liu, Yi-Min; Yu, Xiao-Li (Frontiers in Oncology, 2022)
Background and purpose: No research has evaluated the role of the accessory parotid gland (APG) in nasopharyngeal carcinoma (NPC). We aim to assess the effect of APG on the dosimetric parameters of parotid glands (PGs) and the prediction for late xerostomia. Material and methods: Medical records of 32 NPC patients with radiological evidence of APG treated at Sun Yat-sen Memorial Hospital from November 2020 to February 2021 were reviewed. The APG was delineated on clinically approved treatment plan (PLAN1). PLAN2 was designed based on PLAN1, where APG was willfully protected. Dose-volume parameters of PGs and PGs plus APG were analyzed, and their relationships with xerostomia at 6-9 months after radiotherapy were explored. Results: Fifty APGs were found. The mean volume of APG was 3.30.2 ml. Significant differences were found in every pair of corresponding dosimetric parameters in PLAN1 and PLAN2. When APG was added, the mean dose and percentage of volume receiving more than 30Gy of PGs reduced greatly in PLAN1 and PLAN2 (39.550.83Gy vs. 37.710.75Gy vs 36.400.74Gy; 62.002.00% vs. 57.411.56% vs 55.541.61%;). Three patients were improved to meet the dose constraint in PLAN1, While in PLAN2 the number turned 7. With APG included, the prediction power of dosimetric parameters for xerostomia tended to improve, though no remarkable difference was found. Conclusion: APG has a similar function as the PGs. With the APG included, the dosimetric parameters of PGs improved. It may be favorable to comprise APG in the volume of PGs as an OAR in IMRT of NPC patients.